2016
DOI: 10.1002/14651858.cd010429.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for osteoporosis in people with ß-thalassaemia

Abstract: Treatment for osteoporosis in people with ß-thalassaemia (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…There is no universal consensus regarding when and how to carry out such an assessment for all the pathologies involved. Following the existing guidelines for each pathology is therefore recommended [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…There is no universal consensus regarding when and how to carry out such an assessment for all the pathologies involved. Following the existing guidelines for each pathology is therefore recommended [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Zoledronic acid was administered every 3 months in patients with osteoporosis. This 4-mg dose was administered every 3 months according to current osteoporosis management guidelines ( 15 ). Patients who were unable to continue this course of treatment (often due to adverse events) were given an annual IV dose in its place.…”
Section: Methodsmentioning
confidence: 99%
“…Zoledronic acid has been tested with different dosing regimens (4 mg IV every 3 months or 4 mg IV every 6 months) for osteoporosis management in thalassemia patients ( 11 ). Zoledronic acid 4 mg IV every 3 months is one of the most promising protocols ( 8 - 9 , 12 ) but evidence is lacking with respect to other potential doses (such as IV zoledronic acid administered annually) for the treatment of low BMD associated with thalassemia ( 13 - 15 ). Studies have shown that 5-mg IV zoledronic acid administered once annually can lead to increased BMD and reduced bone resorption and formation in women with postmenopausal osteoporosis ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of energetic particles and radiation from the Sun with the atmospheres of planets, their satellites, and comets produces X-radiation through a number of physical processes: scattering, fluorescence, charge exchange, or the stimulation of auroral activity. Chandra has observedin many cases discovered -X-rays from Venus [26]; the Earth [27] and its moon [28]; Mars [29]; Jupiter [30,31], its aurorae [32], some of its moons [31,32] and the Io plasma torus [31]; Saturn [33,34] and its rings [35]; and numerous comets [36,37]. For overviews of these observations, see e.g.…”
Section: Solar System Objectsmentioning
confidence: 99%
“…Prior to Chandra, the origin of cometary X-rays was debated. Now, observational and theoretical work has demonstrated that charge-exchange collisions of highly charged solar wind ions with cometary neutral species are the best explanation for the observed X-ray emission [32]. Chandra has also been used to discover X-ray signatures of charge exchange in the exospheres of Venus and Mars, enabling measurement of the planetary outgassing rates.…”
Section: Solar System Objectsmentioning
confidence: 99%